Feasibility and usefulness of a leadership intervention to implement evidence-based falls prevention practices in residential care in Canada - Gifford, Wendy; Lewis, Krystina B; Eldh, Ann C; Fiset, Val; Abdul-Fatah, Tara; Aberg, Anna C; Thavorn, Kednapa; Graham, Ian D; Wallin, Lars (Université d'Ottawa | University of Ottawa, 2019)
Abstract Background Leadership is critical to supporting and facilitating the implementation of evidence-based practices in health care. Yet, little is known about how to develop leadership capacity for this purpose. The aims of this study were to explore the (1) feasibility of delivering a leadership intervention to promote implementation, (2) usefulness of the leadership intervention, and (3) participants’ engagement in leadership to implement evidence-based fall prevention practices in Canadian residential care. Methods We conducted a mixed-method before-and-after feasibility study on two units in a Canadian residential care facility. The leadership intervention was based on the Ottawa model of implementation leadership (O-MILe) and consisted of two workshops and two individualized coaching sessions over 3 months to develop leadership capacity for implementing evidence-based fall prevention practices. Participants (n = 10) included both formal (e.g., managers) and informal (e.g., nurses and care aids leaders). Outcome measures were parameters of feasibility (e.g., number of eligible candidates who attended the workshops and coaching sessions) and usefulness of the leadership intervention (e.g., ratings, suggested modifications). We conducted semi-structured interviews guided by the Implementation Leadership Scale (ILS), a validated measure of 12-item in four subcategories (proactive, supportive, knowledgeable, and perseverant), to explore the leadership behaviors that participants used to implement fall prevention practices. We repeated the ILS in a focus group meeting to understand the collective leadership behaviors used by the intervention team. Barriers and facilitators to leading implementation were also explored. Results Delivery of the leadership intervention was feasible. All participants (n = 10) attended the workshops and eight participated in at least one coaching session. Workshops and coaching were rated useful (≥ 3 on a 0–4 Likert scale where 4 = highly useful) by 71% and 86% of participants, respectively. Participants rated the O-MILe subcategories of supportive and perseverant leadership highest for individual leadership, whereas supportive and knowledgeable leadership were rated highest for team leadership. Conclusions The leadership intervention was feasible to deliver, deemed useful by participants, and fostered engagement in implementation leadership activities. Study findings highlight the complexity of developing implementation leadership and modifications required to optimize impact. Future trials are now required to test the effectiveness of the leadership intervention on developing leadership for implementing evidence-based practices.